Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1182/blood.v126.23.1893.1893
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing an Enhanced CAR T Cell Product By Inhibition of the PI3K/Akt Pathway During T Cell Expansion Results in Improved In Vivo Efficacy of Anti-BCMA CAR T Cells

Abstract: Patients treated with chimeric antigen receptor (CAR) T cells targeting CD19 for B cell malignancies have experienced rapid and durable tumor regressions. Manufacture of CAR T cells is challenged by the necessity to produce a unique drug product for each patient. Each treatment requires ex vivo culture of patient T cells to facilitate CAR gene transfer and to achieve therapeutic amounts of T cells. Paradoxically, ex vivo culture with IL-2 also decreases CAR T cell activity. Some investigators have proposed iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Functionally, this was shown to enhance their anti-tumor efficacy and to improve overall survival [82,98]. More recently, ACT has been improved upon to allow for the ex vivo manipulation of CD8 T cells transduced with chimeric antigen receptor (CAR), specific for tumor antigens that are not restricted by MHC Class I (major histocompatibility complex I) [99]. While demonstrated to be effective in the treatment of a number of malignancies, the presence of IL-2 within ex vivo cultures, necessary to maintain viability, has, paradoxically been shown to reduce CAR T cell activity [99].…”
Section: Combination With Immunotherapiesmentioning
confidence: 99%
“…Functionally, this was shown to enhance their anti-tumor efficacy and to improve overall survival [82,98]. More recently, ACT has been improved upon to allow for the ex vivo manipulation of CD8 T cells transduced with chimeric antigen receptor (CAR), specific for tumor antigens that are not restricted by MHC Class I (major histocompatibility complex I) [99]. While demonstrated to be effective in the treatment of a number of malignancies, the presence of IL-2 within ex vivo cultures, necessary to maintain viability, has, paradoxically been shown to reduce CAR T cell activity [99].…”
Section: Combination With Immunotherapiesmentioning
confidence: 99%
“…Ex vivo culture of CAR T cells with 10 μM of LY294002 (PI3K inhibitor) yielded a higher number of T SCM/CM cells and dramatically improved the efficacy of CD33 CAR T cells in vivo [ 16 ]. Interestingly, anti-BCMA CAR T cells cultured in IL-7 and IL-15 failed to control tumour growth in vivo, while CAR T cells preconditioned with IL-2 and PI3K inhibitor demonstrated long-term and complete remission in the mouse model [ 128 ]. Similarly, Akt inhibition in CAR T cells promotes FAO metabolism, dampens glycolysis pathways, reduced glucose uptake, lactate production and downregulating pro-apoptotic genes (BAX and BAD), whilst encouraging T CM differentiation [ 9 , 15 , 129 ].…”
Section: Strategies To Improve Car T Cell Therapy By Metabolic Repmentioning
confidence: 99%
“…In another interesting study, Perkins et al, have shown that culturing of anti-BCMA CAR T cells with IL-2 and PI3K inhibitor (PI3Ki) leads to an increased frequency of CD62L+ CD8 T cells in the final product. Their data revealed that inhibition of PI3K during ex vivo expansion with IL-2 may generate a superior anti-BCMA CAR T cell product for clinical use (57). Likewise, Zheng et al, reported that treatment of CAR T cells with a PI3Ki not only maintains their less differentiation state without affecting their expansion capacity but also improves their persistence in vivo which results in reduction of tumor burden (58).…”
Section: Pharmacological Inhibitorsmentioning
confidence: 99%